Substantial Insect Herbivory in a South African Savanna-Forest Mosaic: A Neglected Topic - Maraia, Heveakore; Charles-Dominique, Tristan; Tomlinson, Kyle W; Staver, Ann Carla; Jorge, Leonardo Re; Gélin, Uriel; Jancuchova-Laskova, Jitka; Sam, Legi; Hattas, Dawood; Freiberga, Inga; Sam, Katerina (Ecology and evolution, 2024)
Insect herbivory plays a crucial role in shaping plant communities in many terrestrial ecosystems. However, in African savannas, insect herbivory has been relatively understudied compared to large mammalian herbivory. In this study, we examined the impact of insect herbivory, focusing on leaf chewers and miners, in a South African savanna-forest mosaic (including patches of forest, thicket and savanna) in Hluhluwe iMfolozi Park, South Africa. Our investigation spanned gradients of rainfall, fire frequency and mammal density. We surveyed a total of 864 woody plants from 48 plant species in 38 plots. Insects consumed 6% of leaf biomass, which is comparable to their impact in temperate broadleaf forests, but the extent of herbivory damage varied between vegetation types. Overall, leaf loss was 70% higher in forests and savanna than that in thicket. Plants in the forests experienced greater damage from chewing insects, whereas miners caused relatively more damage in savannas. Rates of insect herbivory also varied among plant species, declining with carbon and dry matter content but increasing with specific leaf area. Although no significant trade-off was detected between insect and mammal herbivory, plant species with limited physical defences against mammals tended to experience high levels of insect herbivory. Our findings highlight the intricate dynamics of insect herbivory in different vegetation types and suggest that insect leaf herbivory, alongside mammalian herbivory, could play a significant role in influencing plant community composition and overall savanna ecosystem functioning.
Keywords: savanna‐forest mosaic; insect–plant interactions; arthropod herbivory damage; leaf chewers; insect herbivory; leaf miners; ungulates; South Africa